Insights from CPTu and Seismic Cone Penetration Testing in the Kathmandu Valley, Nepal - Gilder, Charlotte E. L.; Pokhrel, Rama Mohan; De Luca, Flavia; Vardanega, Paul J. (Frontiers in Built Environment, 2021)
Seismic hazard assessment often relies on static piezocone penetration tests (CPTu) to estimate the cyclic resistance ratio (CRR) and for the evaluation of in situ soil behavior. This article presents CPTu data acquired in the Kathmandu valley sediments and makes use of established CPTu interpretation procedures to assess the soil in situ properties. Up to this point predominantly SPT data and limited shear wave velocity measurements have been relied upon to assess the variability and seismic response of soil deposits underlying Kathmandu. This article provides 1) additional data to add to the existing SAFER/GEO-591 database, 2) new shear-wave velocity measurements, and 3) initial estimates of CRR at the sites visited. Based on the work presented in this article, it is concluded that a more detailed methodology is needed for liquefaction assessment mainly due to the presence of saturated silts in the valley.